An overview on open science in the European rail sector - Sánchez Martín, Celestino; Calonge Cases, David; Milenković, Miloš (Transport, 2023)
Despite the increasing relevance of Open Science (OS) in the European research landscape, very few publications have addressed the analysis of its role within the European rail context. To this effect, the present paper aims at contributing to shed light on the topic by setting the cornerstone for a differentiated analysis of OS in this sector. In order to do so, the analysis is divided into 2 main sections. The 1st provides an overview of initiatives and experiences regarding OS, which have been recently carried out in the sector. The analysis of initiatives and scientific publications has shown that Open Data (OD) is the area attracting more attention and with more potential for expansion mainly due to the commercial interest of the data. As expected, the use of Open Tools (OT) is common but, interestingly, a growing interest in the development of OT in the sector has been detected. The creation of Open Standards (OSt), developed by specific rail stakeholders’ groups or by coalitions of different stakeholders is increasing in the last years. Amongst the OS areas analysed, Open Access (OA) and Citizen Science (CS) have shown less progress. However, tendencies toward an increasing interest in these areas within the sector has been also detected. The 2nd section aims to uncover the issues or barriers preventing a wider spread of OS specifically in the rail sector and suggest regulatory avenues and actions to overcome them. The identified issues revolve around 3 topics: the lack of initiative on behalf of the European Union (EU) to a) engage other stakeholders beyond the field of research, and b) leverage untapped OS potential in sector-specific situations, which could contribute to its development; and finally, the absence of a sector-specific OS framework. The establishment of such a framework could have a significant positive impact in OD, which is the most appealing area and thus contributing to the uptake of OS as a whole in the sector. In view of such issues, the present paper suggests the establishment of: (1) a European Rail Open Science Policy Platform in order to create a forum-like space in which to align the stakeholder’s positions, and (2) a Joint Rail Data Action Plan to design an OS governance framework, with the aim to ensure the usability, quality, and reliability of data. After identifying the state of OS in the rail sector and the uncovering of several issues that are hindering its development, this paper concludes that the constant further monitoring with regards to needs, challenges and interests (or lack of such) of the different rail stakeholders is key to ensure the continuous development of OS.